Influence of lecithin cholesterol acyltransferase alteration during different pathophysiologic conditions: A 45 years bibliometrics analysis - Gao, Hongliang; Wu, Jing; Sun, Zhenyu; Zhang, Furong; Shi, Tianshu; Lu, Ke; Qian, Dongfu; Yin, Zicheng; Zhao, Yinjuan; Qin, Jian; Xue, Bin (Frontiers in Pharmacology, 2022)
Background: Lecithin cholesterol acyltransferase (LCAT) is an important enzyme responsible for free cholesterol (FC) esterification, which is critical for high density lipoprotein (HDL) maturation and the completion of the reverse cholesterol transport (RCT) process. Plasma LCAT activity and concentration showed various patterns under different physiological and pathological conditions. Research on LCAT has grown rapidly over the past 50 years, but there are no bibliometric studies summarizing this field as a whole. This study aimed to use the bibliometric analysis to demonstrate the trends in LCAT publications, thus offering a brief perspective with regard to future developments in this field. Methods: We used the Web of Science Core Collection to retrieve LCAT-related studies published from 1975 to 2020. The data were further analyzed in the number of studies, the journal which published the most LCAT-related studies, co-authorship network, co-country network, co-institute network, co-reference and the keywords burst by CiteSpace V 5.7. Results: 2584 publications contained 55,311 references were used to analyzed. The number of included articles fluctuated in each year. We found that Journal of lipid research published the most LCAT-related studies. Among all the authors who work on LCAT, they tend to collaborate with a relatively stable group of collaborators to generate several major authors clusters which Albers, J. published the most studies (n=53). The United States of America contributed the greatest proportion (n=1036) of LCAT-related studies. The LCAT-related studies have been focused on the vascular disease, lecithin-cholesterol acyltransferase reaction, phospholipid, cholesterol efflux, chronic kidney disease, milk fever, nephrotic syndrome, platelet-activating factor acetylhydrolase, reconstituted lpa-i, reverse cholesterol transport. Four main research frontiers in terms of burst strength for LCAT-related studies including “transgenic mice” ， “oxidative stress”, “risk” and “cholesterol metabolism “need more attention. Conclusion: This is the first study that demonstrated the trends and future development in LCAT publications. Further studies should focus on the accurate metabolic process of LCAT dependent or independent of RCT using metabolic marker tracking techniques. It was also well worth to further studying the possibility that LCAT may qualify as a biomarker for risk prediction and clinical treatment.